Leriche Syndrome in the emergency department: Two case reports - Yilmaz, Mustafa; Gurger, Mehtap; Atescelik, Metin; Goktekin, Mehmet Cagri; Yigit, Ihsan (Derman Medical Publ, 2017)
Leriche syndrome, resulting in occlusion of the aortic bifurcation, is a rarely seen peripheral vascular disease that is treated surgically and causes severe morbidity and mortality. It is characterized by claudication in one or both lower extremities and by absent or decreased femoral pulses. It should be considered in the differential diagnosis in patients with complaints of pain or weakness in the lower extremities.
Acil serviste leriche sendromu: İki olgu raporu
Keywords: Emergency Service; Leriche Syndrome; Thrombosis